2020
DOI: 10.1007/s00259-020-04948-y
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-labelled desferrioxamine-B for bacterial infection imaging

Abstract: Purpose With the increase of especially hospital-acquired infections, timely and accurate diagnosis of bacterial infections is crucial for effective patient care. Molecular imaging has the potential for specific and sensitive detection of infections. Siderophores are iron-specific chelators recognized by specific bacterial transporters, representing one of few fundamental differences between bacterial and mammalian cells. Replacing iron by gallium-68 without loss of bioactivity is possible allowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
80
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(91 citation statements)
references
References 43 publications
9
80
0
2
Order By: Relevance
“…A recent study of Petrik et al also shows the promising application of 68 Ga(III)/DFOB complex for molecular imaging by the PET technique in animal models. These results also revealed the potential application of the 68 Ga(III)/DFOB complex for the molecular imaging of different bacterial infections, including Pseudomonas aeruginosa and Staphylococcus aureus [ 87 ].…”
Section: Dfob In Medicinal Chemistry and Other Applicationsmentioning
confidence: 98%
“…A recent study of Petrik et al also shows the promising application of 68 Ga(III)/DFOB complex for molecular imaging by the PET technique in animal models. These results also revealed the potential application of the 68 Ga(III)/DFOB complex for the molecular imaging of different bacterial infections, including Pseudomonas aeruginosa and Staphylococcus aureus [ 87 ].…”
Section: Dfob In Medicinal Chemistry and Other Applicationsmentioning
confidence: 98%
“…Any new diagnostic probe must be evaluated against a reliable "gold standard," so we compared the specificity of our probe with the clinically available 18 F-FDG. We noticed that, unlike 64 Cu-YbT, 18 F-FDG accumulated uniformly in muscles harboring pathogenic bacteria, irrespective of their Gram specifications or species differences (Figure 2, F-H). Subsequently, we compared sensitivity of 64 Cu-YbT to 18 F-FDG by administering the probes in mice infected with 10 3 , 10 4 , 10 5 , and 10 6 cfu of 2 different FyuA-expressing bacteria, E. coli UTI89 and K. pneumoniae.…”
mentioning
confidence: 91%
“…We noticed that, unlike 64 Cu-YbT, 18 F-FDG accumulated uniformly in muscles harboring pathogenic bacteria, irrespective of their Gram specifications or species differences (Figure 2, F-H). Subsequently, we compared sensitivity of 64 Cu-YbT to 18 F-FDG by administering the probes in mice infected with 10 3 , 10 4 , 10 5 , and 10 6 cfu of 2 different FyuA-expressing bacteria, E. coli UTI89 and K. pneumoniae. Figure 3 shows the rapid detection of as little as 10 4 cfu of both E. coli UTI89 and K. pneumoniae by 64 Cu-YbT within 2 hours, which is similar to the detection sensitivity of 18 F-FDG.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The siderophore-based iron uptake system differs between bacterial and mammalian cells. Petrik et al [1,6] demonstrated that deferoxamine, a siderophore marketed under the brand name Desferal (DFO), can be radiolabeled with gallium-68 without loss of bioactivity. In vitro characterisation was tested in different microbial cultures, whereas in vivo biodistribution was studied in healthy mice.…”
Section: Innovationmentioning
confidence: 99%